2023
DOI: 10.1002/adhm.202300935
|View full text |Cite
|
Sign up to set email alerts
|

Black Phosphorus Nanosheets Assist Nanoerythrosomes for Efficient mRNA Vaccine Delivery and Immune Activation

Abstract: Messenger RNA (mRNA)‐based vaccines have enormous potential in infectious disease prevention and tumor neoantigen application. However, developing an advanced delivery system for efficient mRNA delivery and intracellular release for protein translation remains a challenge. Herein, a biocompatible biomimetic system is designed using red blood cell‐derived nanoerythrosomes (NER) and black phosphorus nanosheets (BP) for mRNA delivery. BP is covalently modified with polyethyleneimine (PEI), serving as a core to ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…To solve the problem of easy degradation and expression of RNA, RNA structure can be modified, such as through codon optimization [41], nucleotide modification [42], appropriate modification of structural elements (UTR's, 5 ′ capping, ORF, Poly(A) tail) [43], or piggybacking with liposomes [44], nanosheets [45], and so on.…”
Section: Rna/dna-based Neoantigen Vaccinesmentioning
confidence: 99%
“…To solve the problem of easy degradation and expression of RNA, RNA structure can be modified, such as through codon optimization [41], nucleotide modification [42], appropriate modification of structural elements (UTR's, 5 ′ capping, ORF, Poly(A) tail) [43], or piggybacking with liposomes [44], nanosheets [45], and so on.…”
Section: Rna/dna-based Neoantigen Vaccinesmentioning
confidence: 99%
“…BP was covalently modified with PEI and served as the core to efficiently condense mRNA via electrostatic interactions, forming NER@BPmRNA. In in vivo experiments, they demonstrated that NER@BP, when injected into the muscle, effectively targeted the spleen for antigen delivery [ 162 ].…”
Section: Nanomaterials For Nucleic Acid Deliverymentioning
confidence: 99%
“…Compared with other nanomaterials, black phosphorus nanosheets (BP) have a higher surface-to-volume ratio due to the wrinkled lattice configuration, which could increase the drug loading capacity [ 10 ]. For instance, Yang et al [ 11 ] designed a biocompatible biomimetic system for mRNA delivery using red blood-cell-derived nanoerythrocytes (NER) and BP, and the results showed that systematic delivery of coronavirus receptor-binding domain (RBD) mRNA significantly improved antibody titers and pseudovirus neutralization compared with NER without BP assistance. Therefore, BP could be used as a safe and effective delivery tool for RNA-based therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, BP could be used as a safe and effective delivery tool for RNA-based therapies. However, BP itself was also reported to be easily oxidized and degraded to nitrite ions and phosphate and naked BP with negative charge cannot efficiently load and deliver RNA [ 6 , 11 ], which could be avoided by PEI modification since PEI is positively charged and could accomplish lysosomal escape through the “proton sponge effect” [ 12 ]. For example, Wang et al used a survivin siRNA delivery system based on PEI-functionalized BP nanosheets to effectively inhibit tumor growth by silencing survivin expression [ 13 ].…”
Section: Introductionmentioning
confidence: 99%